Property Tax in Transition countries: The Case of the Republic of Macedonia from 2006-2015 - Elezi, Shiret (European Scientific Journal, ESJ, 2016)
Municipalities to develop their policies use Local taxes, fees and charges for empower of these potential sources of revenue: local tax autonomy makes collection more efficient and enables municipalities to introduce their own measures of social policy. These sources of income also increase the responsibility of local authorities: Among the various fees, charges and income tax, property tax has become an important source of funding for local costs. In most cases, the various taxes on immovable property- together with other forms of taxes property- established in the new fiscal framework of modern local governments. The fiscal autonomy of local governments is largely defined by the volume of their own sources of income. Own revenue sources limit the dependence of municipalities from intergovernmental transfers and revenues that the municipalities receive from the national budget. I will try to explain hanges made from the decentralization process in Macedonia throught ten years of starting implementation of the decentralization on property tax collection.